Detection of Polymorphisms in MTHFD1 G1958A and Its Possible Association with Idiopathic Male Infertility - Khaki, Amir Afshin; Tanoomand, Asghar; Hajibemani, Abolfazl; Abouhamzeh, Beheshteh (Urology Journal, 2019)
Purpose: The role of male infertility is important in human infertility pathology. Spermatogenesis is a complex developmental process which is regulated by a number of genes. Methylenetetrahydrofolate dehydrogenase1 (MTHFD1) is involved in the synthesis of purine, pyrimidine, and methionine. The aim of this study was to identify the MTHFD1, G1958A polymorphism and its association with idiopathic male infertility in Iranian population. Materials and Methods: This case-control study was conducted on 200 Iranian men, 100 cases with idiopathic infertility (experimental group) and 100 normal men (control group). The subjects were assessed for the MTHFD1 G1958A polymorphism, using the polymerase chain reaction-restriction fragment length polymorphism technique (PCR-RFLP). The chi-square test was used to determine the association between MTHFD1 G1958A polymorphism and male infertility, using SPSS software. P ? 0.05 was considered significant. Results: Totally, the frequency of A allele and AA homozygous genotype was found 51% and 47.3% respectively, with 52.5% and 30% in the experimental group versus 42% and 21% in control group. There was a statistically significant correlation between the frequencies of A allele (95 % CI = 1.028- 2.265, OR = 1.526, p = 0.035) and AA homozygous (% CI = 0.995- 4.494, OR = 2.114, 95 p = 0.05) genotype with the MTHFD1 G1958A polymorphism (P ? 0.05). Conclusion: These results suggest that the polymorphism in MTHFD1 G1598A gene could be considered as an important genetic disorder associated with the etiology of male infertility.